Uma problemática comunicacional entre o judiciário e o cidadão comum: o caso do instituto do jus postulandi - Marinho, Cristhiano Alessi Rabelo (Universidade do Vale do Rio dos Sinos, 2020)
When a citizen appeals to the judicial body to solve a conflict without the presence of a lawyer, the State is committed to addressing him directly. For this reason, the institute of jus postulandi was created, that is the ability given to someone to postulate, before the judicial authorities, his/her claims in court, without the assistance of a lawyer. However, it is impossible to deny that Brazilian legislation was written for all citizens, based on the language adopted in Brazilian law with a lot of slangs, legal terms and expression in Latin. This language complexity, plus the lack of knowledge in the discursive genders in which is involved the judicial proceeding of the participants, in the proceeding development and its steps, becomes an obstacle to ordinary citizens, hindering the understating and the access of those who resort the judicial. Therefore, the aim of this research is to verify how the construction of meanings of the language act in the law field takes place in judicial proceedings of the Special Court of Governador Valadares/MG, when one of the parties is not represented by a lawyer. For that, it is used the Semiolinguistic Discourse Theory (SDT) in which the language is an act that involves the participation of the subjects who interact socially and produce the senses from this interaction. According to the French linguist’s thoughts, Patrick Charaudeau, who proposes an ordinary language phenomenon analysis model based on three levels: the situational, the discursive and the semiolinguistic, judicial proceedings with jus postulandi were analyzed, considering the situational, discursive and textual issues involved in the production of the language act in the legal field. The results of our analyzes suggest that the jus postulandi is submitted to an extremely complex and technical system, which draws itself from judicial argumentation. If for the ones who work in the law field it is a hard task to understand the complexity of the argumentative game, what will be said about the ordinary citizen, who does not understand the legal world in all its dimension.
Keywords: Jus postulandi; Teoria semiolinguística de discurso; Discurso jurídico; Semiolinguistic discourse theory; Legal discourse; ACCNPQ::Lingüística, Letras e Artes::Lingüística